2006
DOI: 10.1007/s11242-005-2809-8
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Viscous Coupling in Two-phase Flow through Porous Media

Abstract: Theoretical analysis is presented to quantify the viscous coupling effect in twophase flow through porous media. The analysis is based on the principle of potential difference equations as well as on the interfacial contact area and partition concept. The analysis shows that viscous coupling effect is negligible throughout the normalized saturation range. The expression, Xφ 2 , was developed for the quantification of the parameter that controls the amount of viscous coupling, where X was theoretically found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…1 The viscous coupling effect means the momentum transfer between the two fluids. 2 To account for viscous coupling effects, usually four dimensionless relative-permeability parameters k ij are used to measure the effective permeability of two-phase flow. They are defined by modifying Darcy's law as in 3 u i =−͚ j =1 2 ͑kk ij G j / j ͒, where i and j indicate phase 1 or 2 and u i is the average velocity of fluid phase i.…”
Section: A Two-phase Flow In Porous Mediamentioning
confidence: 99%
“…1 The viscous coupling effect means the momentum transfer between the two fluids. 2 To account for viscous coupling effects, usually four dimensionless relative-permeability parameters k ij are used to measure the effective permeability of two-phase flow. They are defined by modifying Darcy's law as in 3 u i =−͚ j =1 2 ͑kk ij G j / j ͒, where i and j indicate phase 1 or 2 and u i is the average velocity of fluid phase i.…”
Section: A Two-phase Flow In Porous Mediamentioning
confidence: 99%
“…Theoretical analysis showed that the viscous coupling has significant effects on two‐phase flow in a single‐capillary (Ehrlich, ). However, its effect on two‐phase flow in porous media is very small (Ayodele, ; Bentsen, ; Rakotomalala et al, ), which is controlled by the square of porosity (Ayodele, ; Rakotomalala et al, ). The capillary coupling means the coupling of pressures that takes place across the interfaces located in a porous medium (Bentsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The capillary coupling means the coupling of pressures that takes place across the interfaces located in a porous medium (Bentsen, ). The capillary coupling is reported to be dependent on the porosity of the porous media and hence has more significant effects on two‐phase flow in porous media compared with the viscous coupling (Ayodele, ; Bentsen, ). Because the interfacial coupling occurs at the interfaces between fluids, its effect on two‐phase flow is strongly related to the fluid distribution.…”
Section: Introductionmentioning
confidence: 99%
“…All of these parameters have already been defined by Bentsen (2001Bentsen ( , 2005, Ayodele and Bentsen (2004), Zhang et al (2005), and Ayodele (2006). Two continuity equations:…”
Section: Mathematical Formulationsmentioning
confidence: 99%